2016
DOI: 10.1158/1078-0432.ccr-15-0190
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cancer Stem Cells in Castration-Resistant Prostate Cancer

Abstract: Purpose Clinical evidence suggests an increased CSC in tumor mass may contribute to the failure of conventional therapies since CSCs seem to be more resistant than differentiated tumor cells. Thus, unveiling the mechanism regulating CSCs and candidate target molecules will provide new strategy to cure the patients. Experimental design The stem-like cell properties were determined by a prostasphere assay, and dye exclusion assay. To find critical stem cell marker and reveal regulation mechanism, basic biochem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 49 publications
(61 reference statements)
2
66
0
Order By: Relevance
“…Treatment of DAB2IP-deficient PCa cells with high-dose radiation even at 10 Gy, showed no significant apoptosis [10]. In addition, downregulation of DAB2IP increased the EMT and enriched the cancer stem cell population of the PCa cells [50]. This established line of evidence indicates that DAB2IP knockdown-induced radioresistant PCa cells could be successfully used to evaluate the mechanism underlying the potential radiosensitization induced by PSE and RV.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of DAB2IP-deficient PCa cells with high-dose radiation even at 10 Gy, showed no significant apoptosis [10]. In addition, downregulation of DAB2IP increased the EMT and enriched the cancer stem cell population of the PCa cells [50]. This established line of evidence indicates that DAB2IP knockdown-induced radioresistant PCa cells could be successfully used to evaluate the mechanism underlying the potential radiosensitization induced by PSE and RV.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CD44 antibodies have been utilized as one means of specifically targeting the CSC population (Arabi et al., 2015, Liu and Jiang, 2006, Molejon et al., 2015). Other approaches to target the CSC population via CD44 have been based on altering transcriptional pathways regulating CD44 expression including Wnt (Yun et al., 2016), FOXP3 (Zhang et al., 2015), SMURF1 (Khammanivong et al., 2014), and Bmi-1 (Yu et al., 2014). Our current findings indicate that SUMO inhibitors can repress expression of CD44 in the CSC population through a TFAP2A-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in prostate cancer research have identified resident cancer stem-like cells that are intrinsically resistant to standard treatments and reseed tumor growth following ablative therapies (Chen et al, 2016; Collins et al, 2005; Yun et al, 2016). Furthermore, gene profiling analysis has shown that prostate cancer increases in a stem-like state as it progresses from organ-confined to metastatic disease (Smith et al, 2015).…”
Section: Introductionmentioning
confidence: 99%